2020
DOI: 10.3390/app11010172
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Growth-Inhibiting Bacteria against the Toxic Dinoflagellate Alexandrium catenella (Group I) in Akkeshi-Ko Estuary and Akkeshi Bay, Hokkaido, Japan

Abstract: The distribution of growth-inhibiting bacteria (GIB) against the toxic dinoflagellate Alexandrium catenella (Group I) was investigated targeting seagrass leaves and surface waters at the seagrass bed of Akkeshi-ko Estuary and surface waters of nearshore and offshore points of Akkeshi Bay, Japan. Weekly samplings were conducted from April to June in 2011. GIBs were detected from surface of leaves of the seagrass Zostera marina in Akkeshi-ko Estuary (7.5 × 105–4.7 × 106 colony-forming units: CFU g−1 wet leaf) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Free-living ( Sakami et al, 2017 ) and epiphytic bacteria with algicidal and antifouling properties are abundant on macroalgae or seagrasses ( Inaba et al, 2017 ; Imai et al, 2021 ), and there is evidence that they may regulate biofouling by algae (reviewed by Tarquinio et al, 2019 ). Negative correlations between seagrass beds and algal abundance further suggested that algicidal bacteria associated with these beds may have some control over the growth of algae in the environment ( Inaba et al, 2018 ; Onishi et al, 2021 ), and the potential for development of management strategies to control HABs ( Imai et al, 2021 ), as discussed in more detail below.…”
Section: Control Of Harmful Algal Blooms By Algicidal Bacteria In The...mentioning
confidence: 99%
“…Free-living ( Sakami et al, 2017 ) and epiphytic bacteria with algicidal and antifouling properties are abundant on macroalgae or seagrasses ( Inaba et al, 2017 ; Imai et al, 2021 ), and there is evidence that they may regulate biofouling by algae (reviewed by Tarquinio et al, 2019 ). Negative correlations between seagrass beds and algal abundance further suggested that algicidal bacteria associated with these beds may have some control over the growth of algae in the environment ( Inaba et al, 2018 ; Onishi et al, 2021 ), and the potential for development of management strategies to control HABs ( Imai et al, 2021 ), as discussed in more detail below.…”
Section: Control Of Harmful Algal Blooms By Algicidal Bacteria In The...mentioning
confidence: 99%
“…Studies on the distribution of these bacteria have found that they commonly inhabit the coastal waters of Japan, and increase in abundance from peak to termination of red tides, playing a key role in red tide disintegration (Imai et al 1998a(Imai et al , 2001. In fact, many strains of algicidal and growthinhibiting bacteria have been isolated from coastal seawaters in Japan and elsewhere around the world (Imai et al 1993(Imai et al , 1995Imai and Yoshinaga 2002;Mayali and Azam 2004;Inaba et al 2014Inaba et al , 2017Onishi et al 2014Onishi et al , 2021.…”
Section: Environmentally Friendly Strategies Against Habsmentioning
confidence: 99%
“…In the case of the thecate dinoflagellates A. catenella (group I) and H. circularisquama, complete algal kill off is rare, and spherical cells (temporary cysts) are often formed as a result of growth-inhibition activities (Imai et al 1998b(Imai et al , 2020Nagasaki et al 2000; Onishi et al 2014;Inaba et al 2017). Most of the algicidal and growth-inhibiting bacteria belong to the Gram-negative α-proteobacteria, γ-proteobacteria, and the phylum Bacteroides (Imai and Yoshinaga 2002;Mayali and Azam 2004;Imai et al 2006b;Inaba et al 2017Inaba et al , 2019Onishi et al 2021).…”
Section: Environmentally Friendly Strategies Against Habsmentioning
confidence: 99%
“…Additionally, algicidal bacteria may also influence the succession of natural phytoplankton communities (Bigalke et al, 2019;Onishi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that algicidal bacteria play a dominant role in the microbial loop and influence the global cycling of organic carbon in the aquatic environment (Azam et al, 1983 ). Additionally, algicidal bacteria may also influence the succession of natural phytoplankton communities (Bigalke et al, 2019 ; Onishi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%